Influence of Computer Aided Learning for Teacher and Students in Promoting Assimilation of Knowledge. A Critical Literature Review - Makenzie, Alfonso Makenzie (International Journal of Computing and Engineering, 2022)
Purpose: No matter how superior the techniques employed are, it's only through positive attitudes of teachers that the benefits of computer integration into the curriculum instruction could be realized. The overall objective of this study was to examine influence of computer aided learning for teacher and students in promoting assimilation of knowledge. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concluded that all the teachers and majority of the students (93.2%) disagreed to the statement that they had never used a computer and that they were not interested. Based on teachers' perceptions towards the use of computer aided learning all the teachers' strongly disagreed to the statement that computers scare them. Analysis of results showed that the teachers had a positive attitude towards computer aided learning. They therefore agreed that they believed computers were important teaching tool. The study also concluded that he school boards of management were partly involved in the training of teachers on computer aided learning and that the ministry of education also organized training courses for teachers on computer aided learning. Unique Contribution to Theory, Policy and Practice: The study suggests that parents associations (PA) in schools should develop a PA fund and organize equipping schools with more computers and other computer aided learning resources in order to make teaching and learning using computer aided learning easier. The current study suggests that there is need to organize in-service training for teachers in order to equip them with expertise skills and knowledge and build their confidence with ICT tools.